Pengaruh Promosi dan Shopping Lifestyle Terhadap Impulse Buying Pada Konsumen Shopee di Kota Malang - Yesri Rahma Mediantin; Achmad Agus Priyono; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this research was to determine the effect of promotion and shopping lifestyle on impulse buying  for Shopee consumers in Malang. The data source for this research is primary data obtained from answers to questions when distributing questionnaires to Shopee consumers in Malang. The sample method used is purposive sampling and snowball sampling. The number of samples in this study were 130 respondents obtained from the Hair et. al. Methods of data analysis using multiple linear regression analysis with the classical assumption test and hypothesis testing. The results showed: (1) promotion and shopping lifestyle simultaneously had a positive and significant effect on impulse buying for Shopee consumers in Malang, (2) promotion partially had no significant effect on impulse buying for Shopee consumers in Malang, (3) ) shopping lifestyle partially has a positive and significant effect on impulse buying for Shopee consumers in Malang Keywords : Promotion, Shopping Lifestyle, Impulse Buying